(untitled) (Conferencea, 2022)
The development trend of modern society determines the priorities of modernization of education and its quality. Monitoring and diagnostics of the state of educational institutions in order to ensure the level of readiness of students to meet the requirements of society and the state, regular analysis of the objective results of training is an important condition for improving the quality of education. In this regard, pedagogical measures based on the use of tests that allow to ensure a high level of objectivity, fairness and equality in assessing the level of readiness of students and entrants in the process of admission to higher and secondary special, vocational education institutions are particularly important. rin holds. Pedagogical measurement is a field of pedagogy that develops and implements methods and tools for measuring and evaluating the learning outcomes of test takers.